Association between Variations of the Solar Wind Parameters and Geomagnetic Activity Index Аp in 2003–2005 - Falkovich, I. S.; Olyak, M. R.; Kalinichenko, N. N.; Bubnov, I. N. (Видавничий дім «Академперіодика», 2012)
The paper is devoted to comparison of a geomagnetic index Аp with solar wind parameters received from observations during 2003–2005. Some characteristic features of the solar wind geoeffective flows on the decline of the 23rd cycle of solar activity are determined. In particular, the speed of the solar wind geoeffective flows during the observation periods is shown to be on the average lower, and the spatial fluctuations spectrum index higher than that for the quasistationary high-speed solar wind.